On the Dirichlet problem for a quasilinear elliptic second order equation with triple degeneracy and singularity in a domain with edge on the boundary - Borsuk, M.; Portnyagin, D. (Нелинейные граничные задачи, 2000)
Boundedness and Holder continuity of weak solutions have been proved for one quasilinear elliptic second order equation with triple degeneracy and specific singularity in the domain with edge on the boundary. There has been obtained the exact Holder exponent near the edge.